Comparative cytotoxicity of cadmium forms (CdCl2, CdO, CdS micro- and nanoparticles) in renal cells. Issue 1 (13th September 2013) - L'Azou, Béatrice; Passagne, Isabelle; Mounicou, Sandra; Tréguer-Delapierre, Mona; Puljalté, Igor; Szpunar, Joanna; Lobinski, Ryszard; Ohayon-Courtès, Céline
Graphical Abstract: Abstract: Cadmium (Cd) is a potent selective toxicant that preferentially accumulates in the kidneys where it is known to induce cellular injury. The cellular mechanisms explaining toxicity have been well documented by in vivo and in vitro studies. However, experiments have mainly been performed on cadmium chloride (CdCl2 ), while several other forms, such as cadmium oxide (CdO) and cadmium sulfide (CdS), are of interest regarding occupational exposure. CdS is mainly used in nanotechnology, primarily to construct particles known as quantum dots (QDs). The present study focuses on cadmium forms that differ compared to their solubility and their particle size (CdS micro- and uncoated nanoparticles (NPs)), and investigates their effects on mesangial and proximal tubular kidney cells. Cellular toxicity was evaluated by using Neutral Red, MTT and WST-1 assays. Intracellular Cd content was measured using inductively coupled optical emission spectrometry (ICP-OES) and cellular stress was investigated via the effects of Cd complexing bioligands using size exclusion chromatography ICP-MS (SEC-ICP-MS). Data indicated the variability of cytotoxicity responses after CdCl2, CdO, and CdS exposure that were strongly correlated to the cellular Cd content. Release of Cd 2+ linked to solubility and particle degradation were considered to be the cause of these toxicities. The bioinduction of the Cd–MT also evidenced release of Cd 2+ . Our in vitro data identified heterogeneity of Cd toxicity that was dependent on the physico-chemical properties of the form studied and, when considering particle size, constitute an additional step toward the determination of nanoparticle effects in renal cells.